Expanding the Spectrum of EEG Periodic Discharges in Subacute Sclerosing Panencephalitis: A Case Report - Aleksandrova, Iliyana; Asenova, Asya; Deneva, Daniela; Bojinova, Veneta (Journal of Child Science, 2021)
Background Atypical electroencephalogram (EEG) abnormalities emerge in patients with subacute sclerosing panencephalitis (SSPE), especially in cases with an atypical clinical presentation that can lead to diagnostic difficulties.Case Report In this article, we presented a case of SSPE with an atypical onset with epileptic seizures and Parkinson's features. The neurological examination during the initial evaluation of the patient showed extrapyramidal syndrome, hyperreflexia, intention tremor, and dysmetria. Cranial magnetic resonance imaging was normal. Video EEGs were performed in wakefulness and sleep. In wakefulness, multiple brief seizures (1–1.5 seconds were recorded, consisting of gradual bending of the body forward and to the right that lacked the sudden characteristic of myoclonia. During those episodes, we recorded generalized epileptiform activity of 4 or 5 sharp waves, with higher amplitude in the anterior regions, in some of the paroxysms superimposed on a slow wave or followed by a high amplitude slow wave. The paroxysms appeared periodically every 15 to 30 seconds. However, 2 months later, the EEG showed typical periodic generalized activity of biphasic/triphasic slow waves (Radermecker complexes), accompanied by myoclonias.Conclusion We reported a peculiar EEG pattern in a patient with SSPE that consists of periodic generalized activity of sharp waves. Atypical EEG patterns can appear when the disease progresses, but initially too, before typical periodic complexes and can complicate the diagnostic process.
Keywords: EEG periodic discharges; subacute sclerosing panencephalitis; measles